Simultaneous single-pulse observations of radio pulsars - II. Orthogonal polarization modes in PSR B1133+16 - Karastergiou, A; Kramer, M; Johnston, S; Lyne, A; Bhat, N; Gupta, Y (2002)
In this letter, we present a study of orthogonal polarization modes in the radio emission of PSR B1133+16, conducted within the frame of simultaneous, multi-frequency, single-pulse observations. Simultaneously observing at two frequencies (1.41 GHz and 4.85 GHz) provides the means to study the bandwidth of polarization features such as the polarization position angle. We find two main results. First, that there is a high degree of correlation between the polarization modes at the two frequencies. Secondly, the modes occur more equally and the fractional linear polarization decreases towards higher frequencies. We discuss this frequency evolution and propose propagation effects in the pulsar magnetosphere as its origin.